EVALUATION OF THE MINISTRY OF SOCIAL AFFAIRS' PEOPLE'S SCHOOL POLICY IN THE CONTEXT OF THE SOCIAL SECURITY AND EMPOWERMENT SYSTEM - R. Willya Achmad W.; Uga Pratama Gunawan; Umi Hani (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2026)
People's Schools are expected to become a strategic instrument in strengthening the socio-economic independence of communities. This study aims to evaluate the effectiveness of the Ministry of Social Affairs' (Kemensos) People's School policy within the framework of the Social Security System and community empowerment efforts. People's Schools are expected to become a strategic instrument in strengthening the socio-economic independence of communities. This research used a qualitative approach with descriptive methods, through analysis of policy documents, in-depth interviews, and observations of program implementation in the field. The results indicate that the implementation of the Ministry of Social Affairs' People's School policy demonstrates a shift from charitable social assistance to more strategic and sustainable empowerment, by providing inclusive education, boarding facilities, and meeting basic needs for children from extremely poor families to break the intergenerational cycle of poverty. Despite its significant potential as an instrument for improving the quality of human resources through strengthening academics, character, and vocational skills, and supporting the placement of graduates, the program's effectiveness is still hampered by challenges related to the distribution and capacity of educators, governance, selection transparency, and the inadequate involvement of appropriate actors. Therefore, strengthening cross-institutional coordination, increasing teacher capacity, and improving governance are key to ensuring that People's Schools operate more adaptively, accountably, and have a maximum impact on the social empowerment of vulnerable communities.